The Impact of Transformational Leadership on Employee Reactions towards Individual Work Performance : A Conceptual Paper - Hamrila, Abdul Latip; Albert, Apoi (Human Resource Management Academic Research Society, 2019)
Interest in the impact of transformational leadership on employee reactions for decades, been the focus of research studies and variety of countries. Employee reactions are usually defined in this research specifically in terms of organizational commitment, job satisfaction and citizenship behavior. Either while such studies have focused on direct or indirect relationships between the specific factors, there is little evidence of any research, which examines the leadership effectiveness as a serially integrative relationship. This study therefore proposes a more comprehensive model of transformational leadership, which incorporates the key factors of employee reactions. The expectancy theory of motivation is used to expand and clarify the current model of leadership effectiveness. This paper claims that the reactions of employees are crucially nested in the transformational leadership – individual work performance relationship. In particular, the significance of this paper is therefore to develop the serially integrative relationship model between transformational leadership, organizational commitment, organization citizenship behavior, job satisfaction and individual work performance.